Active surveillance of adverse events following immunization (AEFI): a prospective 3-year vaccine safety study - Juny Sebastian; Parthasarathi Gurumurthy; Mandyam Dhati Ravi; Madhan Ramesh (SAGE Publishing, 2019)
Background: Vaccines used in national immunization programs are considered safe and effective but immunization safety has become as important as the efficacy of vaccination programs. The objective of the study was to detect adverse events following immunization (AEFIs) to all vaccines administered to a pediatric population in India. Methods: The prospective active vaccine safety surveillance study enrolled eligible children in the age group 0-5 years receiving vaccination from the immunization center at JSS Hospital, Mysuru. Study participants were monitored at the site for 30 min following vaccination and a telephonic survey was made after 8 days to identify all AEFIs. Causality assessment of the AEFIs were done using a new algorithm developed by the safety and vigilance department of the World Health Organization. Results: The incidence of reported AEFIs was 13.7%. The most frequently reported AEFI was fever ( n  = 3095, 93.2%) with an incidence of 109.7 per 1000 doses of vaccine administered, followed by persistent crying ( n  = 69, 2.4 per 1000 doses of vaccine) and diarrhea ( n  = 57, 2.0 per 1000 doses of vaccine). The majorly implicated vaccine for AEFIs was Pentavac® followed by BCG. Consistent causal association to immunization was observed in 93.4% of cases. Conclusions: A high incidence rate of AEFI was observed in our study population when compared with previous published studies. AEFI surveillance studies help to detect changes in the frequency of adverse events, which may be an alert to consider vaccine quality or identify a specific risk among the local population.